Looking Inside the Labor Market: A Review Article - Howitt, Peter (Journal of Economic Literature, 2002)
When unemployed workers are available, why don't firms cut wages until the excess supply is eliminated? In his book, Why Wages Don't Fall During a Recession, Truman F. Bewley concludes, based on interviews with managers and labor leaders, that the most important factor inhibiting wage cuts is the psychological factor of morale. Bewley's field research has made an outstanding contribution to our knowledge of labor markets, by providing a close-up view of exactly what happens from the vantage point of the participants.